Formulación de una mermelada a partir de pulpa y cáscara de tunas (Opuntia spp.) elaborada a nivel planta piloto - López Orozco, Melva; Mercado Flores, Juan; Martínez Soto, Gerardo; Magaña Ramírez, José Luis (Acta Universitaria, 2011)
After a series of experimental tests of jam pulp-based and peel of prickly pear fruit at a laboratory level, generated from previous research projects, and based on results of sensory evaluation, microbiological and physicochemical analysis, it was selected a formulation for a jam from a mixture of pulp and peel of prickly pear fruit “reyna” variety, and “xoconostle” prickly pear fruit pulp for processing at the pilot platform. The jam produced was characterized by physicochemical analysis and microbiological. In the physicochemical analysis, it was included the determination of dietetic fiber (4.35 g dietetic fiber/15 g jam), being one of the most important evaluation, which value comes mainly from the skin of prickly pear fruit. From the physicochemical analysis, it was designed a label for the jam produced. Based on the specifications required by the “Norma Oficial Mexicana”, the product can be considered suitable for consumption and marketing purposes.
Keywords: Array; Array; Array